Unqualified Skilled Workforce Involvement in Construction Process in South East Nigeria - Onyebuchi Okoro, Chima; Amiri Bin Mansur, Shaiful; Bin Yahya, Khairulan; Sampson Igwe, Uchenna; Ikenna Obiefuna, Jideobi (International Journal of Psychosocial Rehabilitation, 2020)
Skilled workforce competency is one of the critical aspects of labour productivity that requires unbiased attention for effective project delivery in the construction industry. The hazards of involving an unqualified, skilled workforce for the construction process have been considered one of the major contributors to low productivity in the construction industry. This research is aimed at exposing the dangers of involving unqualified skilled manpower in the construction process in south-east Nigeria. The active professionals in the Nigerian construction industry were assessed using a well-structured questionnaire. 250 questionnaires were distributed to the construction professionals, and 213 (85.2%) of the total number of questionnaires distributed was successfully retrieved and analysed. The means and Relative Importance Index (RII) of the data collected from the respondents were calculated to determine the leading factors responsible for the engagement of unqualified skilled workforce for construction processes, criteria for selecting skilled workforce, and the impact of unqualified workforce in the construction process. Based on the opinions of respondents, it was revealed that there is a significant involvement of the unqualified skilled workers in the south-east of Nigeria, and the consequent evidence is the incessant building collapse and poor quality of project delivery in most areas. Therefore, the study recommended that there is an urgent need for the inauguration of skill certification centres where skilled workers will be tested and certified after their training before being deployed into the construction process. On-the-job training and retraining exercises should also be scheduled by the management of every construction industry for regular technological innovation updates and experience sharing for better performance of the skilled workers.